Genre et formes d’hégémonie dans les études sur les stars - Valerio Coladonato (Genre, Sexualité et Société)
This article shows the utility of the concept of hegemony in grasping the political stakes involved in stardom, with specific attention to issues of gender. In the field of star studies, the use of this concept occurs in relation to three types of questions : 1. What is the political value of identification with a star ? 2. What link can be established between socio-economic transformations and the evolution of gender models embodied by stars ? 3. How can we define the dominant meaning of a star ? The utility of the concept of hegemony is brought to the forefront through a critical reading of different theorizations of the link between cinematic identification and power relations. The argument is further sustained by two case studies : the cult which surrounded actor Rudolph Valentino, and the political meaning of Beyoncé.